The β-catenin/YAP signaling axis is a key regulator of melanoma-associated fibroblasts - Liu, Tianyi (Signal Transduct Target Ther, 2019)
β-catenin is a multifunctional protein that plays crucial roles in embryonic development, physiological homeostasis, and a wide variety of human cancers. Previously, we showed that in vivo targeted ablation of β-catenin in melanoma-associated fibroblasts after melanoma formation significantly suppressed tumor growth. However, when the expression of β-catenin was ablated in melanoma-associated fibroblasts before tumor initiation, melanoma development was surprisingly accelerated. How stromal β-catenin deficiency leads to opposite biological effects in melanoma progression is not completely understood. Here, we report that β-catenin is indispensable for the activation of primary human stromal fibroblasts and the mediation of fibroblast-melanoma cell interactions. Using coimmunoprecipitation and proximity ligation assays, we identified Yes-associated protein (YAP) as an important β-catenin-interacting partner in stromal fibroblasts. YAP is highly expressed in the nuclei of cancer-associated fibroblasts (CAFs) in both human and murine melanomas. Mechanistic investigation revealed that YAP nuclear translocation is significantly modulated by Wnt/β-catenin activity in fibroblasts. Blocking Wnt/β-catenin signaling in stromal fibroblasts inhibited YAP nuclear translocation. In the absence of YAP, the ability of stromal fibroblasts to remodel the extracellular matrix (ECM) was inhibited, which is consistent with the phenotype observed in cells with β-catenin deficiency. Further studies showed that the expression of ECM proteins and enzymes required for remodeling the ECM was suppressed in stromal fibroblasts after YAP ablation. Collectively, our data provide a new paradigm in which the β-catenin-YAP signaling axis regulates the activation and tumor-promoting function of stromal fibroblasts.